2015
DOI: 10.18632/oncotarget.5673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin in pediatric epithelial liver tumors: inhibition of tumor growth and alpha-fetoproteinin vitroandin vivoinvolving the NFkappaB- and the beta-catenin pathways

Abstract: In children with hepatocellular carcinoma (pHCC) the 5-year overall survival rate is poor. Effects of cytostatic therapies such as cisplatin and doxorubicin are limited due to chemoresistance and tumor relapse. In adult HCC, several antitumor properties are described for the use of curcumin. Curcumin is one of the best-investigated phytochemicals in complementary oncology without relevant side effects. Its use is limited by low bioavailability. Little is known about the influence of curcumin on pediatric epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…A large number of studies have shown that curcumin has a broad-spectrum anti-tumor effect [ 18 27 ]. Curcumin can not only directly inhibit tumor cell proliferation but also induce cell apoptosis by regulating cell cycle, activating endogenous and exogenous pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that curcumin has a broad-spectrum anti-tumor effect [ 18 27 ]. Curcumin can not only directly inhibit tumor cell proliferation but also induce cell apoptosis by regulating cell cycle, activating endogenous and exogenous pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a natural component extracted from traditional Asian spice turmeric with various potential activities such as anti-oxidant, anti-septic, anti-inflammatory, anti-biotic, anti-amyloid and anti-thrombosis [ 15 17 ]. Recently, researches have proposed its promising anticancer role in colon cancer, breast cancer, liver cancer, head and neck cancer, ovarian cancer, prostate cancer, non-small cell lung cancer, and pancreatic cancer [ 18 27 ]. Despite of being inexpensive and nontoxic, the unfavorable bioavailability which caused by poor absorption, quick metabolism and system elimination restricts the application of curcumin as an anti-cancer agent [ 17 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, in vitro models have shown that curcumin inhibits the growth of a variety of cell lines by inducing cell cycle arrest and apoptosis, most importantly through pleiotropic modulation on several distinct cancer targets including nuclear factor kappa B (NF-κB), cyclooxygenase-2 (COX-2), tumor necrosis factor alpha (TNF-α), STAT-3 and cyclin D1 [2326]. Building upon pre-clinical work, several phase I clinical trials have confirmed both the safety and pharmacokinetics of curcumin in patients with doses escalated up to eight grams per day, and these trials have shown measurable biological effects in patients with a variety of malignancies including pancreatic cancer, multiple myeloma and advanced colorectal cancer refractory to standard chemotherapy [27–30].…”
Section: Curcuminmentioning
confidence: 99%
“…Stable disease in a pediatric HCC patient was seen in a phase I trial of the VEGF‐trapping agent aflibercept . Worth mentioning is the preliminary promise of curcumin in pediatric HCC cell lines and orthotopic models . This phytochemical with few side effects in adult patients has shown antitumor effects in adult HCC.…”
Section: Targeted Therapies In Clinical Trialsmentioning
confidence: 99%
“…40 Worth mentioning is the preliminary promise of curcumin in pediatric HCC cell lines and orthotopic models. 54 This phytochemical with few side effects in adult patients has shown antitumor effects in adult HCC. NFKB1, CTNNB1, and CCND1 are its molecular targets.…”
Section: Ta B L E 2 Molecular Aberrations In Adult and Pediatric Hccmentioning
confidence: 99%